PEMAKZULAN KEPALA NEGARA - Rahman, Abdul (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2017)
Abstract: Impeachment is often interpreted as impeachment, whereas both are academically different. Impeachment is to demand the accountability of the president/ head of state in the context of parliamentary oversight to the president, if the president violates the law. While impeachment means to be relegated or substituted to the state/ government from his post after going through the impeachment process. There are differences and similarities between impeachment concepts in the Indonesian constitution with the concept of Islamic state administration, only the concept offered by Islamic constitution is more universal. Al-Mawardi's thoughts can be used as a new offer to improve the impeachment concept in Indonesia's constitution, namely: (1) the reasons for the dismissal of the president when the president is made political puppet by his family or nearest people; and (2) the implementation or effectiveness of the law when it occurs the dismissal of heads of state from these two concepts provides different political stability. Of the two concepts of the Indonesian constitution provides good political stability with the tempo in the process of trial.